EFEITO DE AGENTES DESSENSIBILIZANTES INCORPORADOS AO ADESIVO NO TRATAMENTO DA HIPERSENSIBILIDADE DENTINÁRIA CERVICAL – ESTUDO IN VITRO E IN VIVO - Zardo, Ligia Nadal (2016)
The dentin hypersensitivity (DH), characterized by discomfort caused by pain, is a common medical condition that requires the professional challenge in choosing appropriate therapy. From this perspective the present study was structured in three stages. The first consisted in the review of the literature available in PubMed, Scielo, Bireme, Cochrane, in order to discuss etiology and prevalence of cervical dentin hypersensitivity, pain mechanism theory and those adopted therapeutic procedures and their effectiveness. The second consisted of an in vitro study to evaluate the physical and chemical characteristics and the potential obliteration of dentinal tubules by desensitizing agents incorporated into the Ambar adhesive. For that were used 72 samples from 36 bovine teeth divided into 6 groups: ambar + SrCl2 group, ambar + NaF group, ambar + SnF2 group, ambar + KNO3 group, ambar + K2C204 group and ambar group. The specimens were prepared for hydraulic conductance test or dentin permeability (n = 30), Scanning Electron Microscopy (SEM) (n = 18), Spectroscopy Micro Raman (n = 12), and energy dispersive spectroscopy (EDS) (n = 12). Data were analyzed with analysis of variance (ANOVA) of one criterion and the significance level was 5%. A reduction in dentin permeability in the treated groups, but no significant differences seen between the groups (p = 0.134). By Micro Raman was possible to observe the behavior of the molecules of chemical compounds of desensitizing salts embedded in the adhesive remained adhered to dentin surface. In the SEM, to dentin surface completely covered and sealed with adhesive and the presence of the desensitizing salts, because the EDS spectrum revealed the presence of NaF and KNO3 clusters dispersed in the adhesive layer. It is concluded from this study that the occlusive agents NaF, SnF2, SrCl2, KNO3, K2C2O4 remained incorporated into the dentin adhesive, although clusters in the adhesive layer, the group was able to obliterate the tubules and reduce dentin permeability. The third stage aimed to identify the desensitizing effect of therapies and monitor the longevity of the effects of desensitizing agents on dentin hypersensitivity. Evaluated desensitizing therapies were: group 1: Ambar + NaF, group 2: Ambar + KNO3; group 3: Low level laser therapy; group 4: Led; group 5: Clinpro XT and group 6: Ambar adhesive. The radomizaded clinical trial, parallel-type, blind placebo-controlled included the participation of 60 patients, with an eligible tooth, causing pain quantified by Verbal Scale of 4 points (VRS) and Numerical Scale of 101 points (NRS 101) after tactile and thermal stimuli immediately after the procedure, 24 hours, 7, 15, 30, 90 and 180 days after the completion of the procedures. The dependent variable intensity of pain against the tactile stimulation (probe) and thermal (water) was analyzed for each trial using the non-parametric test Kruscal- Wallis. In periods when there was a statistically significant difference, the comparison of peer groups was made utilizando- the Mann-Whitney test. The ionomer sealant Clinpro XT was more effective in the immediate reduction of DH, and maintained its long-term effect. The NaF + adhesive and KNO 3 + adhesive groups were effective in the treatment of DH and responded better to treatment than just the Ambar adhesive. At the end of the six-month evaluation, all evaluated desensitizing agents were effective in reducing pain resulting from tooth sensitivity.